Respuesta :

Answer:

(-2, -10) (4, 8) and (6, 14)

Step-by-step explanation:

Remember: (x, y)

Substitute the following numbers in order to solve the equation.

1. (-2, -10)

3 - 6(-2) + 2(-10) = -5

3 + 12 - 20 = -5

15 - 20 = -5

-5 = -5

Correct!

2. (-1, 1)

3 - 6(-1) + 2(1) = -5

3 + 6 + 2 = -5

9 + 2 = -5

11 = -5

Incorrect, X

3. (0, 4)

3 - 6(0) + 2(4) = -5

3 - 0 + 8 = -5

3 + 8 = -5

11 = -5

Incorrect, X

4. (4, 8)

3 - 6(4) + 2(8) = -5

3 - 24 + 16 = -5

-21 + 16 = -5

-5 = -5

Correct!

5. (6, 14)

3 - 6(6) + 2(14) = -5

3 - 36 + 28 = -5

-33 + 28 = -5

-5 = -5

Correct!

We can conclude that:

(x, y)

Substitute the numbers from the paranthesis to the equation and solve!

I hope you understood!!!